Beliefs about willpower moderate the effect of previous day demands on next day’s expectations and effective goal striving - Bernecker, Katharina; Job, Veronika (Frontiers in Psychology, 2015)
Research suggests that beliefs about willpower affect self-regulation following previous self-regulatory demands (Job et al., 2010). Some people believe that their willpower is limited, meaning that after a demanding task it needs to be replenished (limited theory). By contrast, others believe that willpower is not limited and that previous self-control tasks even activate willpower (non-limited theory). We hypothesized that when people experience a demanding day their beliefs about willpower predict their expected capacity to self-regulate and their actual self-regulation on the following day. In a daily diary study (N = 157), we measured students’ daily level of demands, their expected performance in unpleasant tasks, and their effective goal striving. Results showed that following a demanding day, students with a non-limited theory had higher expectations about their progress in unpleasant tasks and were striving more efficiently for their goals than students with a limited theory. These findings suggest that beliefs about willpower affect whether demands experienced on a previous day have positive or negative consequences on people’s self-regulation.